F(x)=12x+7/6x+3

Simple and best practice solution for F(x)=12x+7/6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for F(x)=12x+7/6x+3 equation:



(F)=12F+7/6F+3
We move all terms to the left:
(F)-(12F+7/6F+3)=0
Domain of the equation: 6F+3)!=0
F∈R
We get rid of parentheses
F-12F-7/6F-3=0
We multiply all the terms by the denominator
F*6F-12F*6F-3*6F-7=0
Wy multiply elements
6F^2-72F^2-18F-7=0
We add all the numbers together, and all the variables
-66F^2-18F-7=0
a = -66; b = -18; c = -7;
Δ = b2-4ac
Δ = -182-4·(-66)·(-7)
Δ = -1524
Delta is less than zero, so there is no solution for the equation

See similar equations:

| -9.8t^2-19t-2=0 | | N^2+10n+50=0 | | 6(1-5x)=126 | | 3x-6=x+16 | | 1-3x=26/1-3x | | -2(6k-9)=-12(1+k) | | 1/2x-14=29 | | 8x=(7x-6)=13x-14 | | -5-2(6k-9)=-12(1+k) | | 8x-7x-6=13x+14 | | 5x-23=2(2x+7) | | 9x=2x+3 | | 8x-(7x-6)=(13x+14) | | x/3x-6=2-2x/x-2 | | (x)^1/2=3x-4/4 | | 2(5x+6)=11x+6 | | m3=100-13 | | 4y−3=13 | | x+12=3x-42 | | x/7+48=48 | | b2=100-36 | | x/12+6/8=1 | | 8+3u=17 | | 3u+2=14 | | m3=-64 | | 6x×x-x-2=0 | | x/12=6/8=1 | | 5n+11=4+5n | | Q^d=2000-2.5P | | -5(2k-3)=35 | | 7x=-3(x-2) | | ((x^2-3x+2)/(x-1)^1/2)=0 |

Equations solver categories